THE EFFECT OF SCRAMBLE LEARNING MODEL ON HISTORICAL THINKING ABILITY IN HISTORY SUBJECT IN CLASS X SMA NEGERI 30 KABUPATEN TANGERANG: Pengaruh Model Pembelajaran Scramble Terhadap Kemampuan Berpikir Sejarah pada Mata Pelajaran Sejarah di Kelas X SMA Negeri 30 Kabupaten Tangerang - Agus Rustamana; Arif Permana Putra; Ma`rifatul Hasanah (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to determine the effect of the scramble learning model on historical thinking skills in history lessons in grade X at SMA Negeri 30 Tangerang Regency. The research method used in this study was a quantitative method with a quasi-experimental design, involving two classes, namely a control class and an experimental class. The Non-Equivalent Control Group Design was used, which involved pre-tests and post-tests in both the control and experimental classes. The instrument used was a test (multiple choice) with five indicators of historical thinking skills. This study was conducted in class X.1, which had 36 students as the control class, and class X.6, which had 36 students as the experimental class. The results of the study are as follows: (1) there is an effect of the scramble learning model on students' historical thinking skills, hypothesis testing through a two-tailed t-test using the pooled variance formula with a significance level of α = 0. 05 yielded a t-value of 2,89 > the t-table value of 1,667 with a total value of 1,223, so Ha was accepted and H0 was rejected. (2) The historical thinking skills of students who used the scramble learning model were higher than those of students who used the discovery learning model. The average posttest score for the experimental class was 68,33, and for the control class it was 64,72. It can be concluded that the experimental class had a higher average score than the control class. The scramble learning model can be used as an alternative for history learning at SMA Negeri 30 Tangerang Regency. In implementing the scramble learning model, students are involved in groups to match or pair answers to form the correct answers to the teacher's questions, which is effective in increasing student activity and cooperation.